Variability in Morphological and Phenological Characters of Apricot (Prunus armeniaca L.) Genotypes from Wild Population in Shimla District of Himachal Pradesh - Chauhan, Nirmla; Singh, Dinesh; Kumar, K.; Dogra, R. K.; Bodh, Suman (International Journal of Economic Plants, 2019)
Apricot (Prunus armeniaca L.) is one of the most important stone fruits, basically due to its good taste and multiple uses. Commercial growing of apricots is marred by monoculture owing to predominance of very few cultivars like New Castle, Royal etc. However, there is a wide array of germplasm of apricot growing wild in north-western Himalayas. The ever-changing environment and consumer preferences demand apricots with wider adaptation and better yield and fruit quality. This is necessitated more from crop diversification point of view, and also in view of the widespread use of apricot in processing, thus enhancing farmer’s income. So, efforts were made to select superior genotypes from wild apricots in Shimla district of Himachal Pradesh during 2015–16. Observations on flowering, tree and leaf characters were recorded in 42 genotypes. Late and extended flowering was observed among the selected genotypes. Maximum trunk girth (78.84 cm) was recorded in SCK5 under Chirgaon location. Opening of flower stated from 4th week of February (SRB1, SRB3, SRB4, SR2, STB1, STB2 and STB3) and extended upto 1st week of April (SCK1, SCK3, SCK4, SCK5 and SCK6). These characters can be used for further breeding improvement of apricots like late flowering trait to protect it from spring frost.